Cover. Issue 1 (8th January 2022) - Schoenborn, Nancy L.; Blackford, Amanda L.; Joshu, Corinne E.; Boyd, Cynthia M.; Varadhan, Ravi
Abstract : Kaplan‐Meier analyses of life expectancy for a hypothetical 70‐year‐old woman for each possible combination of comorbidities (none, low/medium, high) and frailty (low, high). See the related article by Schoenborn et al., pages 99–109 .